2022
DOI: 10.31234/osf.io/8f3kr
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The importance of awareness in face processing: A critical review of interocular suppression studies

Abstract: Human faces convey essential information for understanding others’ mental states and intentions. The importance of faces in social interaction has prompted suggestions that some relevant facial features such as configural information, emotional expression, and gaze direction may be processed unconsciously, yielding preferential access to awareness. This evidence has predominantly come from interocular suppression studies, with the most common method being the Breaking Continuous Flash Suppression procedure, wh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 112 publications
0
1
0
Order By: Relevance
“…Previous studies have suggested a processing advantage and faster access to awareness for upright over inverted faces [15][16][17][18][19][20] , and for emotional over neutral faces 21,22 . (Although the latter claim, in particular, has been challenged [23][24][25][26] ). If so, processing -and possibly awareness -of upright and emotional faces should require shorter minimal exposures than inverted and neutral faces, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have suggested a processing advantage and faster access to awareness for upright over inverted faces [15][16][17][18][19][20] , and for emotional over neutral faces 21,22 . (Although the latter claim, in particular, has been challenged [23][24][25][26] ). If so, processing -and possibly awareness -of upright and emotional faces should require shorter minimal exposures than inverted and neutral faces, respectively.…”
Section: Introductionmentioning
confidence: 99%